The role of preparatory knowledge in knowledge management - GUERRACHE, Afaf (Dirassat Journal Economic Issue, 2012)
This study investigates the detection of the role of preparing knowledge management in knowledge management. This role represents the shifting point in the phase of seeking for implicit knowledge in organizations and to transform it to explicit knowledge then to apply and evaluate it; to the phase of searching for knowledge or provoking human abilities within organizations in order to generate implicit and explicit knowledge. Later on, they will be exploited in favor of developing organizations; this latter which gives the form of circle to the knowledge management, because the last phase in any knowledge either implicit or explicit, it represents the evaluation’s phase, however, preparing knowledge relates between applied knowledge evaluation and stimulating brain to search for knowledge which should be applied. In addition, we present deferent definitions in relation with the two terms: knowledge management and preparing knowledge